Odpowiedzi

Najlepsza Odpowiedź!
2009-12-19T21:52:46+01:00
5,
a) (x+7)²
x²+14x+49
(x+7)(x+7)
x²+2*7x+49
x²+49
+16x
b) (2a-3)²
(2a-3)(2a-3)
4a²-12a+9
4a²+9

6)
a) (3x+2)²=3(3x²+5)
3x²+2*3x*2+2²=9x²+15
3x²+12x+4=9x²+15
3x²+12x-9x²=15-4
-6x²+12x=11

b)
3x(3x-4)=(3x-2)²
9x²-12x=3x²-2*3x*2+2²
9x²-12x=3x²-12x+4
9x²-12x-3x²+12x=4
6x²=4 /:6
x²=4/6

c)
(½x-2)²+x=0,25x(x-8)
½x²-2*½x*2+2²+x=0,25x²-2
0,5x²-2x+4+x=0,25x²-2
0,5x²-2x+x-0,25x²=-2-4
0,25x²-x=-6

d)
(0,09y-3,6)y=(2-0,3y)²
0,09y²-3,6y=2²-2*2*0,3y+0,3y²
0,09y²-3,6y=4-1,2y+0,3y²
0,09y²-3,6y+1,2y-0,3y²=4
-0,21y²-2,4y=4

7.
a) 4x-(x-6)²>x(5-x)+5x
4x-x²+2*x*6+6²>5x-x²+5x
4x-x²+12x+36>10x-x²
4x-x²+12x-10x+x²>-36
6x>-36 /:6
x>-6

b)
(2x+4)²<2x(3+x)+2x²+6
2x²+2*2x*4+4²<6x+2x²+2x²+6
2x²+16x+16<6x+2x²+2x²+6
2x²+16x-6x-2x²-2x²<6-16
-2x²+10x<-10